HEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS - A PRESENTATION OF ACCELERATED PHASE OF CHEDIAK HIGASHI SYNDROME; CASE REPORT AND CLINICOPATHOLOGICAL REVIEW - Omer Javed,; Bushra Kaleem,; Sana Naveed,; Anila Aali,; Hamza Khan, (Journal of Ayub Medical College Abbottabad, 2024)
Chediak Higashi syndrome (CHS), a rare form of autosomal recessive disorder has been reported globally in less than 500 cases over the past two decades. It clinically manifests as repeated episodes of infection, haemorrhagic sequelae, partial albinism, photosensitivity and late neurological signs (neuropathy, cognitive impairment etc). The pathognomonic morphological finding is the presence of abnormally large intra-cytoplasmic granules, particularly in leucocytes. Almost 85% of CHS cases advance into an accelerated phase, characterized by cytopenias and hemophagocytosis, leading to multi-organ failure. Case presentation: The child in the present case had consanguinity and a positive family history of recurrent infections. She had repeated episodes of bacterial infections. She also had a history of photosensitivity. CBC reported cytopenias. Peripheral smear showed neutrophils with characteristic large sized abnormal intra-cytoplasmic granules. Bone marrow biopsy was performed which also showed similar granules in leucocytes along with hemophagocytosis. Other clinical and biochemical markers also pointed towards hemophagocytic lymphohistiocytosis (HLH), thus patient was diagnosed as CHS in an accelerated phase. She received eight doses of chemotherapy but eventually expired. Conclusion: The definitive treatment is hematopoietic stem cell transplantation which improves the hematological and immune aspects of CHS but not the neurological. Steps should be taken for early diagnosis and to prevent advancement into the accelerated phase.